Novel technique for continuous pressure monitoring of esophageal balloon in balloon tamponade device for acute variceal bleed. Issue 3 (29th April 2022) - Torres‐Gonzalez, Brian H.; Powell, Thomas L.; Yee, Jennifer; Hunold, Katherine M.
Abstract: Acute variceal bleeding is a life‐threatening emergency associated with high mortality. Balloon tamponade is required for refractory bleeding to allow stabilization for definitive therapy. Unfortunately, these devices are associated with iatrogenic complications such as esophageal necrosis and perforation. It is imperative to accurately measure the esophageal balloon pressure to limit these complications. We describe a novel technique for both initial and continuous pressure monitoring of the esophageal balloon.